Long-term outcomes of urinary tract infection (UTI) in Childhood (LUCI): protocol for an electronic record-linked cohort study. Issue 4 (20th April 2019) - Lugg-Widger, Fiona V; Angel, Lianna; Cannings-John, Rebecca; Jones, Hywel; Lau, Mandy; Butler, Christopher; Francis, Nick A; Hay, Alastair D; Heginbothom, Margaret; Hood, Kerenza; Paranjothy, Shantini; Vandervoort, Judith; et al.
Abstract : Introduction: Current guidelines advise the prompt diagnosis and treatment of urinary tract infection (UTI) in children to improve both short and longer term outcomes. However, the risk of long-term complications following childhood UTI is unclear. UTI is relatively common but difficult to diagnose in children as symptoms are non-specific. Diagnosis requires a urine sample, but sampling is difficult and infrequent, and it is not clear if sampling should be given greater priority in primary care. The LUCI study will assess the short, medium and longer term outcomes of childhood UTI associated with routine and systematic sampling practices. Methods and analysis: Two data sets will be established. The first will consist of routinely collected data (hospital, general practice (GP), microbiology) from children born and resident in Wales, linked via the Secure Anonymised Information Linkage (SAIL) Databank (an 'e-cohort'). Urine sampling in this data set reflects normal practice 'routine sampling'. Outcomes (including renal scarring, hypertension, end-stage renal failure, hospital admissions, GP consultations, antibiotic prescriptions) for children with at least one UTI confirmed with microbiological culture (mcUTI) or no mcUTI before the age of 5 will be compared. The second will combine data from two prospective observational studies ('DUTY' and 'EURICA') employing systematic urine sampling for children presenting to primary care with acute, undifferentiated illness, linked to routine data via SAIL (Wales) and NHS Digital (England). Outcomes (as above, plus features of mcUTI) for children with an mcUTI in this data set, identified through systematic urine sampling, will be compared with those with an mcUTI identified through routine urine sampling (data set 1). Ethics and dissemination: The study protocol has been approved by NHS Wales Research Ethics Committee and the Health Research Authority's Confidentiality Advisory Group. Methods of innovative study design and findings will be disseminated through peer-review journals and conferences. Results will be of interest to clinical and policy stakeholders in the UK.